Trehalose sustains a higher post‐thaw sperm motility than sucrose in vitrified human sperm. (25th May 2017) - Schulz, M.; Risopatrón, J.; Matus, G.; Pineda, E.; Rojas, C.; Isachenko, V.; Isachenko, E.; Sánchez, R.
Summary: One of the cryopreservation methods that best preserves sperm function is vitrification. However, comparative studies have not been performed to evaluate the effect of nonpermeable cryoprotectors on sperm function for prolonged periods of time post‐devitrification. These times are necessary, especially in in vitro fertilisation and intrauterine insemination, for gamete interaction and then fertilisation to occur, while maintaining motility to arrive at the fertilisation site. In this study, sucrose (.25 m ) and trehalose (.1 and .05 m ) were compared in essential parameters like motility and plasma membrane integrity for 12 hr. Post‐devitrification sperm motility using .1 m trehalose was 68.9%, higher than that obtained with .05 m trehalose (59.9%, p < .0081) and .25 m sucrose (57.9%, p < .0002). Similar results were obtained at 6 and 12 hr with .1 m trehalose (58.0% and 42.3% respectively) compared to .05 m trehalose ( p < .0184 and p < .033) and .25 m sucrose ( p < .0001 and p < .0012).There was no difference between .25 m sucrose and .05 m trehalose. Membrane integrity was best preserved at time 0 by .1 m trehalose ( p < .05), but there was no significance at 6 and 12 hr compared to sucrose. Our results suggest that for assisted reproduction techniques that require motile spermatozoa for a longer period of time, use of .1 m trehalose is recommended in the sperm vitrification technique.